(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Grigorеva M. A. Psychological and pedagogical aspects of intensification of students’ educational activity. The article is devoted to the definition of the essence of the intensification of the educational process and the coverage of psychological and pedagogical aspects of the intensification of students’ learning activities in a higher educational establishment. The ways of improving the content of educational material and teaching methods are suggested.